Aplikasi Perancang Bajet (iBajet) - Zainuddin, Nik Mohamad Hazeel Amirul; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2022)
Budget Planner Application (iBajet) is a mobile application that function to record daily incoming and outgoing transactions such as income and expenses. This application was developed to help individuals, especially youths such as students of institutions of higher learning and newly employed people such as university graduates in managing their expenses and transaction record. This is because, the problem that arises among individuals is that they usually do not record and monitor each of their daily expenses until they forget where all the money has been spent. With this iBajet application, users will be able to record and monitor their daily expenses more clearly and thoroughly. This application will also be able to help individuals in avoiding the occurrence of expenses in excess of the existing budget. This application will be able to be used on various mobile platforms as it is developed with cross-platform development. The model used in the development of this application is the ADDIE model. Meanwhile, application development will be developed using Flutter software, Visual Studio, Android Studio and MySQL database. The programming language used is Dart. The app is expected to be able to assist users in recording their incoming and outgoing transactions, control spending and better plan finances for future use.